The Effectivity of Enterotoxigenic Escherichia coli (Multivalen) Vaccination in Swine Case Study in Bali - Anastasia Sischa Jati Utami; Ida Ayu Parwati; I Nyoman Suyasa (ANIMAL PRODUCTION, 2021)
Swine cattle have high economic advantages and social values ​​ in Balinese society. This study aimed to determine the effectiveness of Enterotoxigenic Escherichia coli (ETEC) vaccine in gestating sows. We used 26 gestating sows aged 1.5 years old at their last trimester assigning 13 sows in the control group and 13 sows in treatment group to receive multivalent ETEC vaccine twice: on the 70-75 days of gestation and a booster on 100-105 days of gestation. Sows with the vaccine treatment divided into 3 group that groups A was treated antifimbrial K41, groups B was antifimbrial 987P, while in group C was Antiimbrial K88. The changes in temperature were observed from one day before to 4 days after vaccination in a randomized block design. To determine the antibody formed, blood samples were taken one and two weeks after the first vaccine and five weeks after the booster. The blood sample was analyzed by the Enzyme Linked Immunosorbent Assay (ELISA) technique. The rates of diarrhea and postnatal mortality were also observed. The results showed that the antibody titer level increased significantly in the fifth week in groups A with titer 1,94 ±0,22 and B with titer 1,98 ± 0,30 , while the number of diarrhea incidents was 0.9% compared to control 34% with a mortality rate of 0%. In conclusion, this multivalent ETEC vaccine is safe to use and has been shown to be effective for ETEC cases in swine.